The effects and economic consequences of cutting R&D tax incentives - Ming-Chin Chen; Huan-Yi Li (China Journal of Accounting Research, 2018)
Research has documented the stimulating effect of R&D tax credits on R&D expenditure when enacting an R&D tax credit or raising the credit rate. However, the potential adverse effects and consequences of reducing R&D tax incentives remain unexamined. Using a cut in R&D tax incentives in Taiwan, we document the adverse effect of reducing the R&D credit rate on corporate R&D expenditure. The reduced R&D credit rate has a negative impact on the relation between corporate R&D expenditure and firm value. Our results highlight the adverse effects and economic consequences of reducing R&D tax incentives in an emerging economy.
Keywords: 650; R&D credit rate; R&D investment; Firm value